Report of the National Seminar Organised by Planning Commission - Planning Commission (Planning Commission, 1965)
The National Seminar on Literacy highlighted the urgent need to address adult illiteracy in India, emphasizing the role of functional education in promoting social and economic development. Co-organized by the Planning Commission and the Maharashtra Government, the seminar examined pre-literacy, literacy, and post-literacy programs, alongside administrative frameworks for adult education. Key findings underscored the disproportionate impact of illiteracy on women and rural populations, the limited scope of basic literacy, and challenges in educational retention. Successful initiatives such as the Gram Shikshan Mohim demonstrated the effectiveness of community-driven, campaign-based approaches. Recommendations focused on establishing a national literacy policy, enhancing community involvement, promoting functional literacy, ensuring adequate resource allocation, and creating a National Board for Adult Literacy to coordinate and monitor programs. The documents stress the importance of a multi-stakeholder, integrated strategy to achieve sustainable literacy, linking education with socio-economic empowerment.
India Planning Commission
India Planning Commission
Keywords: Adult Literacy; National Seminar; Functional Education; Illiteracy; Rural Education; Gram Shikshan Mohim; Policy Recommendations; Community Participation; Resource Allocation; Educational Retention; Campaign Approach; Non-Formal Education